2017
DOI: 10.4103/1735-5362.217426
|View full text |Cite
|
Sign up to set email alerts
|

The silencing effect of miR-30a on ITGA4 gene expression in vitro: an approach for gene therapy

Abstract: Integrins are adhesion molecules which play crucial roles in cell-cell and cell-extracellular matrix interactions. Very late antigen-4 or α4β1 and lymphocyte Peyer’s patch adhesion molecule-1 or α4β7, are key factors in the invasion of tumor cells and metastasis. Based on the previous reports, integrin α4 (ITGA4) is overexpressed in some immune disorders and cancers. Thus, inhibition of ITGA4 could be a therapeutic strategy. In the present study, miR-30a was selected in order to suppress ITGA4 expression. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Integrins exist as two non-covalently bound α and β subunits, which pair to form heterodimers( 4 5 ). Integrins can bind to extracellular matrix (ECM) glycoproteins including collagens, fibronectins, laminins, and cellular receptors such as VCAM-1 and the intercellular cell adhesion molecule (ICAM) family( 5 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Integrins exist as two non-covalently bound α and β subunits, which pair to form heterodimers( 4 5 ). Integrins can bind to extracellular matrix (ECM) glycoproteins including collagens, fibronectins, laminins, and cellular receptors such as VCAM-1 and the intercellular cell adhesion molecule (ICAM) family( 5 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…They are important cell surface receptors. They mediate adhesion of cells to extracellular matrices and adhesion of cell to cell, participate in cell proliferation, differentiation, adhesion, migration and other processes, and play an important role in the growth and development, immune response and other physiological processes of the body [54, 55]. Kim et al [56] found that the down-regulation of ITGA4 in duodenum of chickens infected with Eimeria .…”
Section: Discussionmentioning
confidence: 99%
“…Some important advances in genomic techniques have led to recognize possible biomarkers involved in breast cancer development, progression, and invasion ( 1 2 ). Currently, personalized approaches towards the prediction and management of different subtypes of breast cancer have been developed based on omics data ( 3 4 5 ). Despite significant progress in treatment strategies, certain breast tumors remain resistant to the current treatments due to their heterogeneous nature.…”
Section: Introductionmentioning
confidence: 99%